FORMULASI SABUN MANDI CAIR EKSTRAK KULIT JERUK MANIS VARIETAS SIAM (Citrus sinensis L.) DENGAN VARIASI KONSENTRASI SURFAKTAN SODIUM LAURIL SULFAT - Handayani, Sri; hidayati, Nurul; aprilianti, Rian (Universitas Muhammadiyah Klaten, 2018)
Citrus sinensis L. skin is a high-value waste because it contains vitamin C. The Citrus sinensis L. skin of siam varieties is formulated into liquid soap using sodium lauryl sulfate which acts as a surfactant and as a good foaming agent. The aims of this study are to determine the effect of variations in the concentration of sodium lauryl sulfate surfactant on the quality control test for liquid bath soap. The type of research used is experimental research. This research uses the extract of conjoined sweet orange peel obtained by maceration for 6 days using 70% ethanol solvent and maceration repeated for 4 days so that the extract obtained is more. Liquid soap is made in 3 formulas with varying concentrations of sodium lauryl sulfate. Formula I uses a concentration of 8%, formula II 17% and formula III 26%. The quality control test of the preparation includes organoleptic, pH, specific gravity, viscosity and high foam. The data obtained were statistically analyzed with one-way analysis of variance (ANOVA) with a confidence level of 95%. The results showed that variations in the concentration of sodium lauryl sulfate could affect the quality control test for liquid bath soap. The three formulas of liquid bathing soap extract of sweet orange peel that meet the standard are 2nd formulas, namely black, distinctive odor of orange peel, thick consistency with pH 6, having specific gravity between 1.039-1.095 g / ml, having a viscosity of between 1.10- 7.90 cps and foam height 0.80-2.00 cm.